Pendidikan Inklusif Perspektif Guru Pendidikan Agama Islam di Sekolah Dasar Negeri - Sari, Nopita; Zaenuddin, Zaenuddin; Hamzah, Nur (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe and analyze Islamic Religious Education (PAI) teachers' perspectives on implementing inclusive education at Public Elementary Schools (SDN) in Sungai Rengas Village. The phenomenon of inclusivity in education requires the active role of teachers, including PAI teachers, in shaping the character of all students, including those with special needs. The problem arises when understanding and support for implementing inclusive education in practice remain limited. This study offers a solution that strengthens PAI teachers' competencies through continuous training and collaboration among relevant stakeholders. The study uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation involving PAI teachers and related parties at the school. PAI teachers have a reasonably good understanding of the concept of inclusive education. Their main challenges include a lack of training, limited facilities and infrastructure, and minimal support from assistants. Nevertheless, the teachers are firmly committed to providing fair and inclusive learning services. PAI teachers at SDN Sungai Rengas show good awareness and commitment to inclusive education despite facing various obstacles to its implementation. This research also provides empirical insights into the roles and challenges of PAI teachers in the context of inclusive education. The findings can be a foundation for developing teacher training policies and strengthening stakeholder collaboration to support effective inclusive education.